TAFSIR AYAT WASATHIYYAH DALAM AL-QUR`AN DAN IMPLIKASINYA DALAM KONTEKS MODERASI BERAGAMA DI INDONESIA - Rahmadi Rahmadi; Akhmad Syahbudin; Mahyuddin Barni (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2023)
This article discusses the interpretation of wasathiyyah verses in QS. Al-Baqarah [2]: 143 from several classical, modern, and contemporary mufassir added with a study of the concept of wasathiyyah in the Qur'an. The interpretation of wasathiyyah then looks at the implications for practising religious moderation in Indonesia, where some parties are socializing. The method used in this study is a literature study of tafsir literature and analyzing it comparatively Religious moderation based on the concept of wasathiyyah As has been explained by some mufassir and researchers show that Quranic moderation refers to the character of fairness, balance, balance, choosing the best, the most beautiful, and above all, having a high position, consistency or istiqamah, accuracy, and with that character the Muslim community becomes an example for other societies. The concept of religious moderation socialized in Indonesia has contained various characters mentioned by several mufassir and Qur'an scholars and can be enriched again with several other characters to enhance further and complement the existing wasathiyyah characters. These various wasathiyyah characters need to be socialized and cultured through various channels to become part of the religious tradition of Muslims in Indonesia.